The impact of news, oil prices, and international spillovers on Russian financial markets - Bernd Hayo; Ali M. Kutan (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2002)
This paper analyzes the impact of news, oil prices, and international financial market developments on daily returns on Russian bond and stock markets. First, there is some persistence in both bond and stock market returns. Second, we find that U.S. stock market returns Granger-cause Russian financial markets. Third, growth in oil prices has a positive effect on Russian stock market returns. Fourth, there is a significant economic and statistical influence of a specific type of news on the Russian bond market: Positive (negative) news related to the energy sector raise (lower) daily returns by one percentage point. News from the war in Chechnya, on the other hand, do not appear to have a significant influence on financial markets.
Keywords: C5; G12; G15; F36; 330; financial market behavior; financial market integration; stock market returns; bonds market returns; news; emerging markets; transition economies